2008
DOI: 10.1182/asheducation-2008.1.36
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Evidence for the Off-label Use of Recombinant Factor VIIa (rFVIIa) in the Acute Reversal of Warfarin?

Abstract: A 47-year-old man presents with hypovolemic shock. He takes warfarin as a result of a mechanical mitral valve insertion 5 years prior, his INR at presentation is 8.4 and emergent CT reveals a very large retroperitoneal hematoma. Despite aggressive fluid and transfusion support he continues hypotensive, requiring ionotrope support. You are asked if he should receive recombinant factor VIIa.To examine current best evidence of the effect of recombinant factor VIIa (rFVIIa) on the reversal of warfarin-induced coag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 21 publications
0
26
0
1
Order By: Relevance
“…There is little evidence to support the use of recombinant factor VIIa for this indication. 30 In the absence of bleeding, a prolonged prothrombin time is not an indication for fresh frozen plasma or frozen plasma. In the bleeding patient, these agents will help to achieve hemostasis and provide time for vitamin K to reverse the effect of the antagonist.…”
Section: Treatment Of Isolated Deficiency Of Vitamin K-dependent Protmentioning
confidence: 99%
“…There is little evidence to support the use of recombinant factor VIIa for this indication. 30 In the absence of bleeding, a prolonged prothrombin time is not an indication for fresh frozen plasma or frozen plasma. In the bleeding patient, these agents will help to achieve hemostasis and provide time for vitamin K to reverse the effect of the antagonist.…”
Section: Treatment Of Isolated Deficiency Of Vitamin K-dependent Protmentioning
confidence: 99%
“…93 Finally, the uncertainty on whether the demonstrable effects of rFVIIa on INR correction are accompanied by adequate restoration of thrombin generation compared with PCCs is the cited reason why one guideline has recommended against the routine use of rFVIIa for warfarin reversal in patients with ICH. 23,94 Published reports have indicated effective in vivo hemostasis after administration of rFVIIa in several clinical settings. Jeffers et al 95 randomly assigned 71 patients with liver disease who underwent laparoscopic liver biopsy to receive 1 of 4 doses (5, 20, 80, and 120 g/kg) of rFVIIa given adjuvantly before biopsy.…”
Section: Prothrombin Complex Concentratesmentioning
confidence: 99%
“…94,[99][100][101] In 2005, guidelines that used the Rand/UCLA appropriateness method were developed jointly by the Society for Advancement of Blood Management and the University Hospitals Consortium. 99 The consensus panel agreed that rFVIIa was appropriate for reversal of warfarin anticoagulation in patients with either spontaneous or traumatic intracranial bleeding.…”
Section: Prothrombin Complex Concentratesmentioning
confidence: 99%
“…31 In a review of the available case series and case reports, Rosovsky and Crowther concluded that, while rFVIIa appears to rapidly reverse the abnormal INR, the clinical impact is difficult to ascertain due to small, poorly controlled trials in which conventional therapy, i.e., plasma and vitamin K therapy, was employed concomitantly. 32 An in vitro comparison of the INR reversal with rFVIIa and PCC demonstrated greater clot stability with PCC. This was presumed to be due to the synthesis of thrombinactivatable fibrinolysis inhibitor (TAFI).…”
Section: Recombinant Fviiamentioning
confidence: 97%